A common partitivirus infection in United States and Czech Republic isolates of bat white-nose syndrome fungal pathogen Pseudogymnoascus destructans - Ren, Ping; Rajkumar, Sunanda S; Zhang, Tao; Sui, Haixin; Masters, Paul S; Martinkova, Natalia; Kubátová, Alena; Pikula, Jiri; Chaturvedi, Sudha; Chaturvedi, Vishnu (Scientific reports, 2020)
The psychrophilic (cold-loving) fungus Pseudogymnoascus destructans was discovered more than a decade ago to be the pathogen responsible for white-nose syndrome, an emerging disease of North American bats causing unprecedented population declines. The same species of fungus is found in Europe but without associated mortality in bats. We found P. destructans was infected with a mycovirus [named Pseudogymnoascus destructans partitivirus 1 (PdPV-1)]. The virus is bipartite, containing two double-stranded RNA (dsRNA) segments designated as dsRNA1 and dsRNA2. The cDNA sequences revealed that dsRNA1 dsRNA is 1,683 bp in length with an open reading frame (ORF) that encodes 539 amino acids (molecular mass of 62.7 kDa); dsRNA2 dsRNA is 1,524 bp in length with an ORF that encodes 434 amino acids (molecular mass of 46.9 kDa). The dsRNA1 ORF contains motifs representative of RNA-dependent RNA polymerase (RdRp), whereas the dsRNA2 ORF sequence showed homology with the putative capsid proteins (CPs) of mycoviruses. Phylogenetic analyses with PdPV-1 RdRp and CP sequences indicated that both segments constitute the genome of a novel virus in the family Partitiviridae. The purified virions were isometric with an estimated diameter of 33 nm. Reverse transcription PCR (RT-PCR) and sequencing revealed that all US isolates and a subset of Czech Republic isolates of P. destructans were infected with PdPV-1. However, PdPV-1 appears to be not widely dispersed in the fungal genus Pseudogymnoascus, as non-pathogenic fungi P. appendiculatus (1 isolate) and P. roseus (6 isolates) tested negative. P. destructans PdPV-1 could be a valuable tool to investigate fungal biogeography and the host-pathogen interactions in bat WNS.
Keywords: virové proteiny; zvířata; RNA virová; fylogeneze; mykoviry; Česká republika; Viral Proteins; Spojené státy americké; Phylogeny; Animals; United States; RNA, Viral; Czech Republic; Chiroptera; Base Sequence; dvouvláknová RNA; sekvence aminokyselin; Ascomycota; sekvence nukleotidů; Amino Acid Sequence; Fungal Viruses; RNA, Double-Stranded